Exploring Artistic Practice in Global Communities of the African Diaspora - Auburn E. Ellis (Adult Education Research Conference, 2014)
There are many contemporary issues to address in adult education. This paper explores art-based strategies and the utilization of creativity to expand learning for global communities of the African Diaspora. Benefits of culturally grounded approaches to education are discussed from Asia and the U.S. Fieldwork images can be viewed at auburnaesthetic.com.